Dengue Hemorrhagic Fever in adolescents and young adults in the Department of Internal Medicine, Gadjah Mada - Ahmad H. Asdie Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1973)
A short history of Dengue, the etiology of Dengue Hemorrhagic Fever and the vectors are reviewed. A classification and nomenclature for diseases suspected to be of dengue or chikungunya virus etiology, as suggested by WHO is given.Six cases and two additional cases of Dengue Hemorrhagic Fever in adolescents and young adults are reported.The bone marrow findings in our cases compared with those found in the literature.The pathogenesis of Dengue Hemmorrhagic Fever is reviewed in short.